2015
DOI: 10.1093/brain/awv002
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal death induced by misfolded prion protein is due to NAD+ depletion and can be relieved in vitro and in vivo by NAD+ replenishment

Abstract: The mechanisms of neuronal death in protein misfolding neurodegenerative diseases such as Alzheimer's, Parkinson's and prion diseases are poorly understood. We used a highly toxic misfolded prion protein (TPrP) model to understand neurotoxicity induced by prion protein misfolding. We show that abnormal autophagy activation and neuronal demise is due to severe, neuron-specific, nicotinamide adenine dinucleotide (NAD(+)) depletion. Toxic prion protein-exposed neuronal cells exhibit dramatic reductions of intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 82 publications
1
65
0
2
Order By: Relevance
“…Given these numerous functions, NAD + has been shown to be important in many biological processes, including metabolism (Garten et al, 2009; Mouchiroud et al, 2013), circadian rhythms (Nakahata et al, 2009; Ramsey et al, 2009), and aging (Imai and Guarente, 2014). Relevant to our studies, NAD + has also been shown to be important in neurodegeneration (Alano et al, 2010; Gerdts et al, 2015; Stein et al, 2014; Zhou et al, 2015). However, the role of NAD + in retinal degeneration has been relatively unexplored to date.…”
Section: Introductionsupporting
confidence: 79%
“…Given these numerous functions, NAD + has been shown to be important in many biological processes, including metabolism (Garten et al, 2009; Mouchiroud et al, 2013), circadian rhythms (Nakahata et al, 2009; Ramsey et al, 2009), and aging (Imai and Guarente, 2014). Relevant to our studies, NAD + has also been shown to be important in neurodegeneration (Alano et al, 2010; Gerdts et al, 2015; Stein et al, 2014; Zhou et al, 2015). However, the role of NAD + in retinal degeneration has been relatively unexplored to date.…”
Section: Introductionsupporting
confidence: 79%
“…Similarly, evaluation of an immunomodulatory or neuroprotective compound between 90 and 120 dpi could provide key information about the relationship between activated microglia and neuronal death in prion disease. 4 The results reported herein contribute to a sizable body of work describing the time course of prion disease. A great deal has been done to identify early biomarkers of disease in cattle, 40e42 cervids, 43,44 primates, 45 sheep, 46 and rodent models of TSEs.…”
Section: Temporal Separation Of Key Events In Prion Diseasementioning
confidence: 68%
“…A toxic monomeric alpha-helical form of PrP ("TPrP") has been deduced from refolding unglycosylated recombinant PrP and assay upon the PK-1 subline of N2a neuroblastoma cells (27). Toxicity mediated by TPrP was observed in the range of 0.5 to 5 g/ml (27,28), which is in the same general range as PrP C levels measured here in brain homogenates of Prnp ϩ/ϩ and Prnp 0/ϩ mice (i.e., ϳ1.1 and 0.4 g/ml, respectively; Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…A calibration curve was prepared with either recombinant PrP(23-231, 129M) for samples containing full-length PrP Sc or recombinant PrP(90-231, 129M) for samples containing truncated rPrP Sc [PrP (27)(28)(29)(30)] after proteinase K (PK) treatment. The PK-untreated sample containing PrP was divided into a native and a denatured aliquot, where the latter was denatured with 4 M guanidinium HCl for 5 min at 80°C.…”
Section: Methodsmentioning
confidence: 99%